A Cytosolic Sensor, PmDDX41, Binds Double Stranded-DNA and Triggers the Activation of an Innate Antiviral Response in the Shrimp Penaeus monodon via the STING-Dependent Signaling Pathway - Soponpong, Suthinee; Amparyup, Piti; Kawai, Taro; Tassanakajon, Anchalee (Frontiers in Immunology, 2019)
Helicase DDX41 is a cytosolic sensor capable of detecting double-stranded DNA in mammals. However, the function of DDX41 remains poorly understood in invertebrates. In a previous study, we identified the first DDX41 sensor in the black tiger shrimp Penaeus monodon (PmDDX41) and showed that it played a role in anti-viral response. In the present study, we demonstrated that PmDDX41 was localized in the cytoplasm of shrimp hemocytes. However, PmDDX41 was localized in both the cytoplasm and nucleus of hemocytes in the presence of white spot syndrome virus (WSSV) infection or when stimulated by the nucleic acid mimics, poly(dA:dT) and poly(I:C). Similar results were observed when PmDDX41 was transfected into human embryonic kidney 293T (HEK293T) cells. Immunoprecipitation further demonstrated that PmDDX41 bound to biotin-labeled poly(dA:dT) but not poly(I:C). The overexpression of shrimp PmDDX41 and mouse stimulator of interferon gene (MmSTING) in HEK293T cells synergistically promoted IFN-β and NF-κB promotor activity via the DEADc domain. Co-immunoprecipitation (Co-IP) also confirmed that there was an interaction between PmDDX41 and STING after stimulation with poly(dA:dT) but not poly(I:C). Our study is the first to demonstrate that PmDDX41 acts as a cytosolic DNA sensor that interacts with STING via its DEADc domain to trigger the IFN-β and NF-κB signaling pathways, thus activating antiviral innate immune responses.